2006
DOI: 10.1002/app.22035
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of impregnation with Imersol‐Aqua on the modulus of elasticity in bending

Abstract: The aim of this study was to investigate the effects of impregnation with Imersol‐Aqua (I‐AQUA) on the modulus of elasticity in bending of some woods. For our study, Oriental beech (Fagus orientalis Lipsky), oak (Quercus petrea Liebl.), Scotch pine (Pinus sylvestris Lipsky), Uludağ fir (Abies Bornmülleriana Lipsky), Oriental spruce (Picea orientalis Lipsky), and poplar (Populus nigra L.) wood samples were prepared according to TS EN (Turkish Standards; European Norm) 408 and impregnated with I‐AQUA by the meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Other defined parameters of wood preservatives, such as its toxicity against wood-destroying agents and its leaching, as well as aging, should be examined. Ors et al (2005) and Var (2013) studied wood that was treated with Imersol-Aqua and SNGW, respectively, and reported that such treatments increased the values of retention, density, and moisture content. Hence, it was concluded that the results in Table 2 were consistent with the reported data in the literature.…”
Section: Physical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other defined parameters of wood preservatives, such as its toxicity against wood-destroying agents and its leaching, as well as aging, should be examined. Ors et al (2005) and Var (2013) studied wood that was treated with Imersol-Aqua and SNGW, respectively, and reported that such treatments increased the values of retention, density, and moisture content. Hence, it was concluded that the results in Table 2 were consistent with the reported data in the literature.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…To date, much research has been conducted on the physical, mechanical, shrinking and swelling properties of various impregnated wood species. Examples of these species are European beech, pine, spruce, Scots pine, yellow poplar, and red oak treated with waterborne preservatives such as chromated copper arsenate (CCA), ammoniacal copper arsenate (ACA), ammoniacal copper zinc arsenate (ACZA), and alkaline copper quaternary (ACQ) compounds (Winandy, 1995); pine treated with linseed oil (Megnis et al, 2002); yellow pine treated with CCA, ACQ-1900, ACQ-2200, Tanalith-E 3491, and Wolmanit CX-8 (Yildiz et al, 2004); oriental beech, oak, Scots pine, oriental spruce, and Uludag fir treated with Imersol-Aqua (Ors et al, 2005); pine and American beech treated with copper chloride, sodium borate, and phenol-formaldehyde resinpyrolytic oil (Mourant et al, 2007); jack pine and sugar maple treated with copper chloride, copper chloride-sodium borate mixture, and phenol formaldehyde-pyrolytic oil resins (Mourant et al, 2008); beech and pine treated with aqueous solution of borates (Simsek et al, 2010); rowan treated with Tanalith-E, Vacsol Azure, Imersol-Aqua, borax, and boric acid (Keskin et al, 2013); fir treated with citric acid (Ville et al, 2014); oriental beech treated with Turkish sweetgum balsam as an aromatic resinous wood preservative (Degirmentepe et al, 2015); and beech, walnut, poplar, ash, and pine treated with Tanalith-E (Keskin and Daglioglu, 2016); shrinking and swelling minimization of wood treated with the synthetic resin-forming materials (Stamm and Seborg, 1936); beech wood impregnated with NH3 (Bariska, 1975); Corsican pine wood treated with ammonia (Coles and Walker, 1978); swelling of wood in liquid ammonia (Stamm, 1955). Some of the wood preservatives mentioned above are now prohibited in several countries, and are being used less frequently in other countries due to their negative impacts to the environment.…”
Section: Introductionmentioning
confidence: 99%